The Effect of Work-Life Balance and Social Competence on the Psychological Well-Being of Public Service Employees - Chiyem Lucky Nwanzu; Sunday Samson Babalola (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
The psychological well-being of the employees is well deserved, as it has numerous positive effects on organisational performance. This understanding calls for research that would identify plausible precursors of psychological well-being. The outcome of such research activities would provide guides for the positive manipulation of psychological well-being to enhance organisational functioning. Therefore, this study aims to investigate whether there is an association between work-life balance and employee psychological well-being and whether social competence plays a role in this relationship. One hundred and fifty employees aged 23 to 56 comprised 52% of men and 76% of married. The survey was self-administered, and the study was cross-sectional. Established scales on work-life balance, social competence, and psychological well-being were used in the study. The data were subjected to regression analysis based on PROCESS Macro. Given the findings, work-life balance and social competence have a favourable relationship with an employee's psychological well-being. In addition, social competence accounted for more variation in employee psychological well-being than work-life balance. According to interaction statistics, social competence moderates the connection between work-life balance and psychological well-being. The findings indicate that the psychological well-being of employees is improved by work-life balance and social competence.